Decarbonization Pathways in Southeast Asia: New Results for Indonesia, Malaysia, Philippines, Thailand and Viet Nam - Francesco Bosello; Carlo Orecchia; David A. Raitzer (Fondazione Eni Enrico Mattei (FEEM), 2016)
Southeast Asia is one of the most vulnerable regions of the world to the impacts of climate change. At the same time, the region is also following a trajectory that could make it a major contributor to greenhouse gas emissions in the future. Understanding the economic implications of policy options for low carbon growth is essential to formulate instruments that achieve the greatest emissions reductions at lowest cost. This study focuses on five developing countries of Southeast Asia that collectively account for 90% of regional emissions in recent years—Indonesia, Malaysia, the Philippines, Thailand, and Viet Nam. The analyses are based on the CGE economy-energy-environment model ICES under an array of scenarios reflecting business as usual, fragmented climate policies, an approximately 2.4°C post 2020 global climate stabilization target, termed 650 parts per million (ppm) carbon dioxide (CO2) equivalent (eq), and an approximately 2°C global target (termed 500 ppm CO2 eq). Averted deforestation through reducing emissions from forest degradation and deforestation (REDD) is included in some scenarios. The study shows that global and coordinated action is found to be critical to the cost effectiveness of emissions stabilization policies. A 650ppm stabilization scenario (below 3°C in 2100) has a similar cost to the region to current fragmented targets, but achieves much higher levels of emissions reductions. However, only some of the countries have short-term emissions targets that are consistent with a stabilization scenario at 650ppm: these are Indonesia, Philippines and Viet Nam. None of the countries' mid-term targets are coherent with more ambitious stabilization scenario at 500ppm.
Keywords: Q54; Q58; C68; 330; Climate Change Mitigation; Asian Economies; Computable General Equilibrium Models